Building and Strengthening Teacher Communities: Improvement Plan for the Profile Journal - Melba Libia Cárdenas (Profile: Issues in Teachers' Professional Development)
Scientific or academic publications have become the best accepted media for scientific and academic communities—mainly established in universities or research centers—to share the knowledge they create and give it greater visibility worldwide. That is, these journals are at the core of scientific communication, which requires permanent assessment of the editorial work and careful planning bearing in mind the responsibilities and needs of the stakeholders that are involved in the production and use of these periodical publications. In this article, I share an improvement plan for the Profile journal, whose purpose is to strengthen the journal’s editorial management and, thus, support the generation and consolidation of communities of teacher researchers.